Vernacular architecture in second home design in Kish Island, Iran - Afshar, Ali (2013)
Kish, which is located in the south of Iran, is an island that has more than one thousand year history of architecture. It is known as one of the most important free trade-tourism zones and holiday destinations of the country, and it has become an increasingly popular destination for investment in housing. According to official statistical reports, all the houses in the island are generally known as second homes for their owners. Modern development in Kish Island has led to the destruction of vernacular architecture and the loss of intellectual capital that flows from this. The main issue in this context is that most of the houses do not correspond with their owners’ requirements especially in the context of local circumstances. This research posits that the vernacular architecture of Kish Island, through its adaptation over a long time to local context, has the potential to provide a more appropriate response than the mis-constructed styles that are currently undermining the architectural design of the second homes in the island. It also emphasizes on the physical and socio-cultural aspects of the vernacular architecture in relation to second homes, the owners and their interaction. Therefore, the study utilized qualitative or quantitative research methods although preliminary qualitative methods were used to answer the research questions, “How can vernacular architecture be applied in designing the contemporary second homes in Kish Island?” The research used a qualitative research methodology to identify the features of the Kish Island’s vernacular architecture as well as to find the relationships between the vernacular architecture and second homes. The research also used the quantitative method to support the qualitative methods and to select units of analysis. As a case study, this study selected Kish Island in Iran and sought to develop architectural solutions to contemporary second home design problems with using adapted vernacular solutions. The research outcome is a series of guidelines for developing second home design solutions to address the contemporary design problems. The suggested outputs for second home design not only improve its quality for answering owners’requirements but also employ second home design for enhancing local architecture. Finally, the research provides a theoretical and experimental approach to support the development of practical and competent constructions in the architectural design field. The implications of the research to the design of second homes are important while advocating the suitability of human requirements which has not been completely investigated and the expected results could be contributed to a specific cultural and geographical domain of Iran, as well as countries in the Persian Gulf region.